Identification of QTLs for root and shoot traits in RIL population of rice (Oryza sativa L.) - Sinha, Sweta; Verulkr, S.B.; Kotasthane, A. S. (The Indian Journal of Genetics and Plant Breeding, 2016)
In present study, quantitative trait loci (QTL) analysis was carried out using 93 SSR and 11 SNP markers in F7 recombinant inbred lines derived from a cross between two potential indica genotypes, Danteshwari and Dagad Deshi. Fourteen putative QTLs identified for 7 root and shoot traits on chromosomes 1, 2, 4, 5, 6 and 8, explained 3.77%-29.24% phenotypic variance at LOD score of > 2.5. The number of putative QTLs was 2 for each root volume, root dry weight, shoot length, shoot fresh weight and total plant length, 1 for root/shoot fresh weight ratio and 3 for root/shoot dry weight ratio. Identified putative QTLs for root and shoot traits in this study provide insight into the mode of drought tolerance, which will accelerate the rice molecular breeding.